2007
DOI: 10.1007/s12043-007-0043-3
|View full text |Cite
|
Sign up to set email alerts
|

On relativistic models of strange stars

Abstract: The superdense stars with mass-to-size ratio exceeding 0.3 are expected to be made of strange matter. Assuming that the 3-space of the interior space-time of a strange star is that of a three-paraboloid immersed in a four-dimensional Euclidean space, we obtain a two-parameter family of their physically viable relativistic models. This ansatz determines density distribution of the interior self-gravitating matter up to one unknown parameter. The Einstein's field equations determine the fluid pressure and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 20 publications
6
33
0
Order By: Relevance
“…For that purpose, we have calculated model parameters (see Tables 1, 2 and 3) by choosing the radius of the compact stars R X J 1856-37,S AX J 1808.4-3658 (SS2) and S AX J 1808.4-3658 (SS1). The calculated mass in Table 1 of the different compact stars are matched well with the proposed values by Li et al [19], Tikekar and Jotania [20] and Thirukkanesh and Ragel [21]. In Fig.…”
Section: Mass-radius Relationsupporting
confidence: 87%
See 1 more Smart Citation
“…For that purpose, we have calculated model parameters (see Tables 1, 2 and 3) by choosing the radius of the compact stars R X J 1856-37,S AX J 1808.4-3658 (SS2) and S AX J 1808.4-3658 (SS1). The calculated mass in Table 1 of the different compact stars are matched well with the proposed values by Li et al [19], Tikekar and Jotania [20] and Thirukkanesh and Ragel [21]. In Fig.…”
Section: Mass-radius Relationsupporting
confidence: 87%
“…In the present article using the observed parameters [19][20][21] of ultra-dense compact stars like RXJ 1856-37, SAX J 1808.4-3658 (SS1) and SAX J 1808.4-3658 (SS2), we have studied the consistency of the proposed model with these compact stars. One may notice that all these stars are nothing but pulsars.…”
Section: Introductionmentioning
confidence: 99%
“…This approach leads to physically viable and easily tractable models of superdense stars in equilibrium. Tikekar and Jotania [87,88], Jotania and Tikekar [89] showed that the ansatz suggested by Tikekar and Thomas [90] has these features and the general three-parameter solution based on it also leads to physically plausible relativistic models of strange stars. Several aspects of physical relevance and the maximum mass of class of compact star models, based on Vaidya-Tikekar ansatz, for the both isotropic and anisotropic pressures have been investigated in [53,[91][92][93].…”
Section: Introductionmentioning
confidence: 97%
“…The solution is, in fact, a sub-class of the model developed by Pandya et al (2015). Tikekar and Jotania (2007) have shown that the Finch-Skea model can be used to describe ultra-compact stars like 'strange stars' composed of u, d and s quarks.…”
Section: Introductionmentioning
confidence: 99%